2015
DOI: 10.1161/circep.114.002052
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Ectopy Predicts Late Recurrence of Atrial Fibrillation After Pulmonary Vein Isolation

Abstract: Background-Late recurrence of atrial fibrillation (AF) after radiofrequency ablation remains significant. Asymptomatic recurrence poses a difficult clinical problem as it is associated with an equally increased risk of stroke and death compared with symptomatic AF events. Meta-analyses reveal that no single preablation patient characteristic efficiently predicts these AF recurrences. This study aimed to evaluate the prognostic value of premature atrial complex (PAC) occurrence with regard to the risk of late A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 34 publications
4
34
0
1
Order By: Relevance
“…We demonstrated that high PAC burden after PVI was associated with less LA and LV reverse remodeling in AF patients even without AF recurrence. These results are consistent with the recent studies showing that patients with high PAC burden after PVI had higher risk for late AF recurrence . Gang et al demonstrated that PAC burden at 6 months after PVI was independently associated with a significantly increased risk of late AF recurrence .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We demonstrated that high PAC burden after PVI was associated with less LA and LV reverse remodeling in AF patients even without AF recurrence. These results are consistent with the recent studies showing that patients with high PAC burden after PVI had higher risk for late AF recurrence . Gang et al demonstrated that PAC burden at 6 months after PVI was independently associated with a significantly increased risk of late AF recurrence .…”
Section: Discussionsupporting
confidence: 92%
“…High prevalence of PAC causes palpitation, which can be associated with reduced quality of life. Furthermore, recent studies showed that frequent PAC after PVI increased the risk of late AF recurrence . We hypothesized that frequent PAC after PVI procedure may attenuate the LA and LV reverse remodeling benefited from maintenance of sinus rhythm.…”
Section: Introductionmentioning
confidence: 97%
“…Non-PV triggers which were not targeted during the initial ablation may manifest as PACs during the ERAA period post-ablation, and may predict late AF recurrence. Gang et al[31] examined 7-d Holter monitors in 124 patients six months post-PVI (3 mo after the blanking period had ended) and found that frequent premature atrial complexes (PACs) strongly predicted late AF recurrence. Patients who developed late recurrence had a median of 248 PACs per day compared vs those without late recurrence (77 PACs per day).…”
Section: Mechanisms and Pathophysiology Of Eraamentioning
confidence: 99%
“…The predictive value of AES for development of AF recurrences was mainly examined after PVI in patients with PAF, whereas the present study evaluates the value of AES prior to PVI in both PAF and PeAF patients. Gang et al showed in a prospective study in 220 patients with PAF that ≥142 AES/day on the 6 months Holter recording was associated with a higher risk of AF recurrences after PVI (HR 2.84). However, the relation between AES prior to PVI and the long‐term AF‐free survival after PVI was not yet described.…”
Section: Discussionmentioning
confidence: 99%